2004
DOI: 10.1111/j.1469-8749.2004.tb00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific cognitive deficits are common in children with Duchenne muscular dystrophy

Abstract: A neuropsychological assessment was conducted to study cognition, with emphasis on memory, information processing/learning ability, and executive functions in boys with Duchenne muscular dystrophy (DMD). A group of 20 boys with DMD, aged 7 to 14 years (mean age 9 years 5 months, SD 2 years 2 months), was contrasted with 17 normally developing age‐matched comparison individuals, using specific neuropsychological tests (Block Span, Digit Span, Story Recall, Rey Auditory Verbal Learning Test, Rey Complex Figure T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0
8

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 25 publications
3
24
0
8
Order By: Relevance
“…The results reported herein, however, contradict another study that found limited executive functions in boys with DMD. 8 Conversely, on the verbal level, we also found restrictions in executive functions. 6,8 Our participants performed very poorly on the subtest ''phonemic verbal fluency" of the RWT, in which the boys had to produce as many words as possible starting with the letter ''s".…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The results reported herein, however, contradict another study that found limited executive functions in boys with DMD. 8 Conversely, on the verbal level, we also found restrictions in executive functions. 6,8 Our participants performed very poorly on the subtest ''phonemic verbal fluency" of the RWT, in which the boys had to produce as many words as possible starting with the letter ''s".…”
Section: Discussionmentioning
confidence: 86%
“…8 Conversely, on the verbal level, we also found restrictions in executive functions. 6,8 Our participants performed very poorly on the subtest ''phonemic verbal fluency" of the RWT, in which the boys had to produce as many words as possible starting with the letter ''s". However, such restrictions in verbal fluency are discussed controversially in the literature.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Impairments in working or short-term memory and limited verbal/auditory span have been highlighted as cardinal features of the neurocognitive profile in DMD, even in individuals with an IQ within the normal range, suggesting a link with the full-length brain dystrophin commonly lost in all patients (Hinton, De Vivo, Nereo, Goldstein, & Stern, 2000;Hinton, De Vivo, Nereo, Goldstein, & Stern, 2001 however, suggest the presence of a broader deficit in higher-order cognitive processing capabilities, specifically in executive function, which might constitute a core endophenotype leading to cognitive deficits in DMD (Donders & Taneja, 2009;Mento, Tarantino, & Bisiacchi, 2011;Wicksell, Kihlgren, Melin, & Eeg-Olofsson, 2004). Executive functions refer to a set of control processes that optimize performance in cognitive tasks, mediate adapted and flexible behaviors and contribute to the temporal encoding and effortful processing in working memory required for response selection.…”
Section: Introductionmentioning
confidence: 98%
“…Interestingly, in a study on variation in educational services receipt among U.S. children with developmental conditions (autism spectrum disorder, developmental delay, and intellectual disability), Lindly, Sinche, and Zuckerman (2015) observed that children with intellectual disability were more likely to have received one or more school-based therapies (OT, PT, social skills training, ST, or language therapy) than those with autism and developmental delay, while children with developmental delay were less likely than the rest of the sample to have received one or more school-based therapies. While we did not measure the level of intellectual delay/disability in our study sample, we do know that 20-50% of boys with DMD are diagnosed with cognitive deficits (Wicksell et al, 2007). Evaluating cognitive deficits and the receipt of therapies for cognitive disorders was beyond the scope of our study.…”
Section: Males With Dmdmentioning
confidence: 99%